Genetic Diversity and Haplotype Analysis of Cattle Hydatid Cyst Isolates Using Mitochondrial Markers in Turkey - Kesik, Harun Kaya; Celik, Figen; Kilinc, Seyma Gunyakti; Simsek, Sami; Ahmed, Haroon; Shen, Yujuan; Cao, Jianping (Mdpi, 2022)
Echinococcus granulosus sensu lato (s.1.) causes cystic echinococcosis in ungulates and humans. The current study was designed to find the genetic diversity and haplotypic profiles of hydatid cysts from the lungs of cattle in three provinces in eastern Turkey. Individual cyst isolates (n = 60) were collected from infected cattle lungs after slaughter and then samples were stored in ethanol (70%) until further use. From each isolate, total gDNA was extracted from the cysts' germinal layers. A partial (875 bp) mt-CO1 gene was amplified by PCR and sequenced unidirectionally. The final size of the trimmed sequences was 530 bp for 60 sequences. Sequence and haplotype analyses were performed, followed by phylogenetic analyses. According to BLAST searches, all sequences were detected as E. granulosus s.s. (G1 and G3 strains). Forty-nine point mutations were identified. In addition, five conserved fragments were detected in all sequences. The haplotype analysis diagram showed E. granulosus s.s. haplotypes organized in a star-like configuration. The haplotypes were characterized by 1-17 mutations compared with the fundamental focal haplotype. Thirty-three haplotypes were determined in 60 samples of which 17 (28.3%) belonged to the main haplotype (Hap_06). The mt-CO1 sequences revealed 49 polymorphic sites, 34.5% (20/49) of which were informative according to parsimony analysis.
Keywords: hydatid disease; Echinococcus granulosus sensu stricto; cattle; haplotype; Turkey